If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2x = 41 Solving 5 + 2x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 41 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 41 + -5 2x = 41 + -5 Combine like terms: 41 + -5 = 36 2x = 36 Divide each side by '2'. x = 18 Simplifying x = 18
| -2=4k | | 6m+2=-98 | | 5+2x=42 | | A+2=-a-1 | | (3x-3)(4x+5)= | | 6/2.5=54/x | | -2f+6=20 | | -6(2x-5)=18 | | -6=9q | | log^5(x+12)=3 | | y=(2x+1)(x-4) | | -2.6/y=1.3 | | 8x-4=2(3x-4) | | 4x^2-2x=e | | 9x-2x=-9-19 | | x-5=36+6 | | ln(4x^2)-ln(2x)=1 | | .04(x^2)+.8x=60 | | 4(3x+5)=8x-22-2x | | 16x-(-4+7x)= | | 7x+2-3+5+3.4=2x-x+12 | | (13x-1)+(9-3x)= | | x^2+4x=357 | | p+6=91 | | -12-2=4u-6u | | 15m+17=9m+83 | | 4(9v+2)=6(1+6v) | | -5x-4x=63 | | 3=n^2-2 | | 2+4+6x=36 | | -15=-4x-17 | | 3x+2-2-x=x-x-4-2 |